Firm Value in Indonesian Healthcare Companies: Do Internal Factors and Dividend Policy Matter? - Ari Nurwahidah; Riri Mayliza; Ahmad Fayaz Naziry; Tran Thai Ha Nguyen; Muhammad Firmansyah (Research in Accounting Journal (RAJ), 2026)
This study aims to analyse the influence of profitability, firm size, leverage and insider ownership on firm value, with dividend policy as a moderating variable, amongst healthcare sector companies listed on the Indonesia Stock Exchange for the period 2020–2024. The study employs the Signalling Theory and Agency Theory approaches, using a sample of 8 companies selected via purposive sampling, yielding 40 observations from the companies’ annual reports, which were analysed using fixed-effects panel data regression via EViews. The results indicate that profitability has a positive effect on firm value, whilst firm size and leverage have no effect. Managerial ownership was found to have a negative effect on firm value. In terms of moderation, dividend policy did not strengthen the effects of profitability, firm size and leverage, but it did strengthen the effect of insider ownership on firm value. An Adjusted R-Squared value of 87.9% indicates that the variables in the model are highly effective in explaining firm value.